ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA PADA OPERASI BILANGAN BULAT DI KELAS II SEKOLAH DASAR NEGERI 72 PALEMBANG - Muhrom Adhytia; Lusiana Lusiana; Tanzimah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The difficulties experienced by students in mathematics are difficulties in calculations, difficulties in understanding the contents of the questions and difficulties in remembering mathematical formulas. Based on the results of the interview, the difficulty in mathematics regarding integer operations is that students are not used to solving integer operation problems. The aim of this research is to determine the results of the analysis of students' learning difficulties in integer operations in class II of the 72 Palembang state elementary school. The method used is a qualitative method using interview and documentation data collection techniques. The results of the research show that difficulties in integer operations include errors in understanding the concept, errors in writing numbers, errors in calculations, students still have difficulty understanding the questions given, students are not used to solving integer operation problems, and students' lack of interest in learning. mathematics.